Propuesta de reforma del artículo 188 del código de trabajo ecuatoriano referente a las indemnizaciones por despido intempestivo - Parreño Morales, Marco Edisson (2017)
The dismissal is an unfair legal concept which uses the employer to provide for early terminate the employment contract agreed with an employee, the dismissal is done without established legal cause and contravening the procedure outlined in the law for termination of the contract Individual work. By this act the employer separates the worker from the employment relationship affecting its stability, leaving him unemployed. Legislation to repair somehow this unjust and unilateral decision obliges the employer to cancel financial compensation and perfecting the illegal dismissal, made with further that violate workers' rights, also affecting his family. Thus this research has allowed us to develop a scientific-legal study on the consequences that causes a worker's dismissal without notice, and unjust compensation. Besides obtaining the various criteria on the possibility of a reform of the Labour Code so that in compensation for unfair dismissal the value to cancel fairer for the loss of loss of livelihood is employment as the detriment of other rights such as employer contribution to IESS and the benefits of social security benefits, thereby seeking to make up for lost something right.